The Influence Of Product Price And Quality On Consumer Satisfaction In Local Clothing Brand In Indonesian E-Commerce : Case Studyin The City Of Semarang - Mukhamad Kholil Aswan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This research aims to see the influence of price and product quality on consumer satisfaction with local clothing brands in Indonesian e-commerce in the city of Semarang. Partially analyzing the influence of price on consumer satisfaction, analyzing the influence of product quality on consumer satisfaction. simultaneously analyzing price and product quality on consumer satisfaction. Descriptive analysis and multiple linear analysis were also used in this research. Descriptive analysis of each variable item. Multiple linear test analysis looks at the overall impact of the independent variable and dependent variable. This research data uses a questionnaire with a sample size of 100 respondents spread across all cities in Semarang. The sampling technique is convenience sampling.The results of the partial analysis can be concluded that there is a positive and significant influence between the price variable on consumer satisfaction. There is a positive and significant influence of product quality variables on consumer satisfaction. The results of simultaneous or joint analysis show a significant influence between price and product quality variables on consumer satisfaction. Competitive prices and good product quality will provide consumer satisfaction with local clothing brands in Indonesian e-commerce in the city of Semarang.